A T-cell–directed chimeric antigen receptor for the selective treatment of T-cell malignancies - Mamonkin, Maksim (Blood, 2015)
Options for targeted therapy of T-cell malignancies remain scarce. Recent clinical trials demonstrated that chimeric antigen receptors (CARs) can effectively redirect T lymphocytes to eradicate lymphoid malignancies of B-cell origin. However, T-lineage neoplasms remain a more challenging task for CAR T cells due to shared expression of most targetable surface antigens between normal and malignant T cells, potentially leading to fratricide of CAR T cells or profound immunodeficiency. Here, we report that T cells transduced with a CAR targeting CD5, a common surface marker of normal and neoplastic T cells, undergo only limited fratricide and can be expanded long-term ex vivo. These CD5 CAR T cells effectively eliminate malignant T-cell acute lymphoblastic leukemia (T-ALL) and T-cell lymphoma lines in vitro and significantly inhibit disease progression in xenograft mouse models of T-ALL. These data support the therapeutic potential of CD5 CAR in patients with T-cell neoplasms.